2006
DOI: 10.1007/s11172-006-0580-9
|View full text |Cite
|
Sign up to set email alerts
|

Combined application of 2D NMR correlation methods and ab initio chemical shift calculations to the structure determination of new heterocyclic compounds

Abstract: The combined use of 2D NMR correlation methods and ab initio chemical shift calcula tions is efficient and, in some cases, virtually the only way to determine the structures of new organic compounds. This approach enabled us to establish the structure of the major unusual product of the three component reaction of imidazo[1,5 a]quinoxalin 4 one, bis(2 chloro ethyl)amine hydrochloride, and potassium carbonate in DMF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…The authors [32] suggested two structural hypotheses (22 and 23), which are both in accordance with the molecular formula C 27 H 22 N 4 O 3 and four other structures (18-21) with a molecular formulae differing from that determined from the MS data ( Fig. 12):…”
Section: Examplementioning
confidence: 76%
See 4 more Smart Citations
“…The authors [32] suggested two structural hypotheses (22 and 23), which are both in accordance with the molecular formula C 27 H 22 N 4 O 3 and four other structures (18-21) with a molecular formulae differing from that determined from the MS data ( Fig. 12):…”
Section: Examplementioning
confidence: 76%
“…The same group of authors [32] reported the application of a more complex molecule structure elucidation strategy that was described in their work. [22] A novel organic compound was investigated by 1D and 2D NMR experiments (DEPT, NOESY, COSY, HSQC, HMBC, and HMBC 1 H-15 N).…”
Section: Examplementioning
confidence: 99%
See 3 more Smart Citations